Diversity of resistant determinants, virulence factors, and mobile genetic elements in Acinetobacter baumannii from India: A comprehensive in silico genome analysis - Kumkar, Shital N.; Kamble, Ekta E.; Chavan, Nikeeta S.; Dhotre, Dhiraj P.; Pardesi, Karishma R. (Frontiers in Cellular and Infection Microbiology, 2022)
In India, the frequency of infections associated with multidrug resistant A. baumannii has risen substantially. The use of next generation sequencing (NGS) techniques combined with comparative genomics have great potential for tracking, monitoring, and ultimately controlling the spread of this troublesome pathogen. Here, we investigated the whole genome sequences of 47 A. baumannii from India, including five clinical A. baumannii isolates collected in 2005 and sequenced for this study. In brief, a total of 47 A. baumannii genomes were analyzed for the presence of antibiotic resistance genes (ARGs), virulence factors genes (VFGs), and mobile genetic elements (MGEs) using various in silico tools. The AbaR-type resistance islands (AbaRIs) were detected by examining the environment of the chromosomal comM gene. To explore genetic diversity, we performed eBURST analysis of sequence types (STs) obtained through whole genome multilocus sequence typing (MLST) based on the Pasteur scheme. The whole genome SNPs-based phylogenetic relationship between the genomes was determined. The dominance of A. baumannii isolates belonging to the ST2 (18/47) was observed. Nevertheless, geographically distant, the SNPs-based phylogenetic analysis showed close relatedness between the genomes belonging to similar STs. The in silico analysis predicted an exuberance of ARGs and MGEs carrying resistance genes associated with antibiotics, quaternary ammonium compounds, and heavy metals. The presence of putative VFGs related to adherence, biofilm formation and iron uptake was observed. An increased accumulation of plasmid associated ARGs has been observed in A. baumannii isolates collected after 2014 as compared to the isolates collected in 2005. To summarize, the comprehensive genome analysis in this study provides an essential insight into the resistome, virulome and mobilome of A. baumannii isolates from India.